Efektifitas Terapi Oketani Breast Massage (OBM) Terhadap Peningkatan Produksi ASI : Case Report - Dahlia, Siti; Sukmawati; Hermayanti, Yanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Postpartum mothers often experience obstacles in the process of breastfeeding their babies, namely insufficient or irregular breast milk production which can cause health problems for both the mother and the baby. One effort to increase breast milk production is through Oketani Breast Massage (OBM). This study aims to determine the effectiveness of providing OBM interventions on increasing breast milk production in post-cesarean mothers. This study uses a case report method. Participants in this study were Mrs. W P1A0 post-cesarean due to indications of PEB and breech presentation. Data collection techniques include interviews, physical examinations and supporting examinations. OBM therapy is carried out twice a day for 30 minutes in the morning and evening for 3 days of treatment at the Hospital and evaluation is carried out by observing the frequency and duration of breastfeeding, the frequency of urination and defecation of the baby, the sucking response and the quality of the baby's sleep to determine the increase in breast milk production. Meanwhile, to assess the success of breastfeeding using the LATCH assessment score instrument including breastfeeding attachment, baby swallowing sound, mother's nipple shape, mother's comfort, and baby's position when breastfeeding. The results of the study showed an increase in the frequency and duration of breastfeeding, the frequency of urination and defecation of the baby, the baby's sucking response was adequate and the baby appeared to sleep soundly, and the success of breastfeeding also increased after OBM was performed. OBM is effective in increasing breast milk production in post-cesarean mothers because its working principle is like a baby's sucking by stimulating the pectoralis muscles of the breast and stimulating the hormones prolactin and oxytocin so that breast milk production becomes more and of better quality.